PENINGKATAN KUALITAS WARNA DAN PERTUMBUHAN IKAN ALBINO TIGER BARB (Puntius tetrazona) DENGAN PEMBERIAN PAKAN YANG MENGANDUNG TEPUNG UDANG REBON - Nur Addini; Niken Ayu Pamukas; Mulyadi Mulyadi; Sukarman Sukarman (Fakultas Perikanan dan Kelautan, Universitas Riau, 2017)
This research was conducted from 7th of March to 16th April 2017 at Research Center and Ornamental Fish Aquaculture (BRBIH), Depok - West Java. The objective of the research was to investigate the best of krill meal in fish meal and to increase color qualit y and growth of albino tiger barb (Puntius tetrazona). The method used was experimental method with Completely Randomized Design, with 4 treatment and 3 replications, ie 0%, 10%, 20%, 30% respectively. The fish were reared in aquarium with size of 40 cm x 30 cm x 30 cm (15 liters of water) with density of 10 fish/aquaria. Fish was fed 3 times a day by means of at satiation. Color sampling was done at the beginning and the end of the study, while for growth sampling was done in the beginning and then every 10 days. The results showed that 30% krill meal gave the best color quality effect with L* =56.53, C = 16.60, H = 79.83, and absolute growth weight 0.68 g, absolute growth length 1.02 cm, specific growth rate 2.13% respectively.